Optimal dispatch of integrated energy microgrid considering hybrid structured electric-thermal energy storage. (November 2022) - Dong, Haiyan; Fu, Yanbo; Jia, Qingquan; Wen, Xiangyun
Abstract: Aiming at the problems of low reliability of centralized energy storage and high construction cost of distributed energy storage, an optimal scheduling model of integrated energy microgrid system considering hybrid structure electric thermal energy storage is proposed. Firstly, a hybrid structured energy storage framework is constructed, taking into account the advantages of centralized structure and distributed structure; Secondly, a multi microgrid system model with hybrid energy storage operator is built, regulate electric energy storage and thermal energy storage, and provide energy storage services for microgrids. It can optimize the coupling of multiple energy within the microgrid and improve energy utilization; Thirdly, aiming at the optimal scheduling problem of different stakeholders, a double-level optimization model is established. Among them, the objective of the upper layer is to maximize the income of hybrid energy storage operator, and the objective of the lower layer is to minimize the energy consumption cost of multi microgrid; Finally, the model is analyzed by four different cases. The example results show that the model can effectively improve the income of energy storage operators, reduce the energy consumption cost of microgrid users, reflect the complementary advantages of multiple energy sources, and improve the utilization rate of energy.